PENGARUH MATERIAL FASADE TERHADAP KONDISI RUANG TERHADAP PSIKOLOGI HUMANISTIK PENDIDIKAN PONDOK PESANTREN - Ade Fitriyanti Ulul Azmi; Ruli Saefudin (Jurnal Arsitektur ARCADE, 2023)
Abstract: Islamic Boarding School buildings in general have closed characteristics and are also not conditioned in architectural terms. The layout of the Islamic boarding school can be said to be unorganized, because its development was not accommodated by careful planning. This is reasonable, limited land and also limited ability in land acquisition due to self-financing from cottage managers who are also limited. From this condition, the cottage building will naturally grow and develop according to the limitations of the topographical conditions and limited land as well as the level of students in the annual student admission period. The lack of predictability related to the development of buildings among Islamic boarding schools is able to have an impact on behavior and psychology as well as an impact on the quality of education. Instability in the development of buildings or infrastructure facilities is a driving force for uncontrolled behavior in the Islamic boarding school environment. Bullying, immoral acts to criminality which are now increasingly prevalent among Islamic boarding schools have become a frightening specter for students and the bad image of Islamic boarding schools has become the public's spotlight on the quality of non-formal education, Islamic boarding schools. In order to reduce the negative tendencies that occur as a result of the spatial layout, application is given to building materials with a dense and limited layout according to the characteristics of Islamic boarding schools. Changes through materials on building facades and new nuances in Islamic boarding school buildingsKeyword: Bullying, Psychology Humanistic, Islamic Boarding School.                                        Abstrak: Bangunan Pondok Pesantren pada umumnya memiliki sifat yang tertutup dan juga tidak terkondisikan secara tata ruang arsitektur. Tata ruang pondok pesantren yang dapat dibilang kurang tertata, dikarenakan pembangunannya tidak diwadahi oleh perencanaan yang matang. Hal ini wajar, keterbatasan lahan dan juga keterbatasan kemampuan dalam pembebasan lahan dikarenakan pembiayaan mandiri dari pengelola pondok yang juga terbatas. Dari kondisi ini, maka bangunan pondok secara alami akan tumbuh dan berkembang sesuai keterbatasan dengan kondisi topografi dan keterbatasan lahan serta tingkat santri dalam periode penerimaan peserta didik pertahunnya. Kurang mampunya diprediksi terkait perkembangan bangunan dikalangan pondok pesantren ini mampu memberikan dampak pada perilaku dan psikologi serta dampak pada kualitas Pendidikan. Ketidakstabilan perkembangan bangunan atau sarana prasrana menjadi pendorong perilaku yang tidak terkontrol dalam lingkungan pesantren. Tindak Bullying, tindak asusila hingga kriminalitas yang kini makin marak terjadi dikalangan pondok pesantren menjadi momok menyeramkan bagi para santri serta buruknya image pondok pesantren menjadi sorotan masyarakat luas terhadap kualitas Pendidikan non formal, pondok pesantren. Guna mengurangi kecenderungan negative yang terjadi akibat tatanan ruang diberikan aplikasi terhadap material bangunan dengan tata ruang yang padat dan terbatas sesuai dengan karakteristik bangunan pondok pesantren. Perubahan melalui material pada fasade bangunan serta nuansa baru dalam bangunan pondok pesantren.Kata Kunci: Perundungan, Psikologi Humanistik, Pondok Pesantren.